2006
DOI: 10.1161/01.atv.0000207319.28254.8c
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NO Synthase Deficiency Promotes Smooth Muscle Progenitor Cells in Association With Upregulation of Stromal Cell-Derived Factor-1α in a Mouse Model of Carotid Artery Ligation

Abstract: Background-Endothelial NO deficiency (endothelial NO synthase [eNOS]-knockout [KO]) enhanced smooth musclecell (SMC)-rich neointimal lesion formation in a mouse model of carotid artery ligation (CAL). Recent evidence indicated that stromal cell-derived factor-1␣ (SDF-1␣)-mediated recruitment of circulating SMC progenitor cells substantially contributed to the SMC-rich neointimal hyperplasia induced by vascular injury. The goal of this study was to investigate the effects of eNOS deficiency on the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 55 publications
5
49
0
1
Order By: Relevance
“…29 Both c-kit ( Figure 3C and 3D) and sca-1 (supplemental Figure IA and IB) staining at 7 days after injury were decreased in I, however the decrease in sca-1 staining did not reach significance. We found very few cells positive for CD68 (macrophage marker) or CD45 (general hematopoetic cell marker) with no difference between treatments (data not shown).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…29 Both c-kit ( Figure 3C and 3D) and sca-1 (supplemental Figure IA and IB) staining at 7 days after injury were decreased in I, however the decrease in sca-1 staining did not reach significance. We found very few cells positive for CD68 (macrophage marker) or CD45 (general hematopoetic cell marker) with no difference between treatments (data not shown).…”
Section: Resultsmentioning
confidence: 89%
“…26,29 Insulin increased the number of circulating cells positive for sca-1 (PϽ0.05; Figure 5A) and tended to increase the number of c-kit-positive cells (supplemental Table III). Circulating precursors also contribute to reendothelialization, and it is possible that neointimal formation is reduced by accelerated reendothelialization.…”
Section: Resultsmentioning
confidence: 95%
“…42 We previously reported that smooth muscle cell migration and proliferation were major pathological processes in this Ang II-accelerated vascular remodeling model. 43, 44 Davis et al initially reported that EETs and an s-EH inhibitor, 1-Cyclohexyl-3-dodecyl Urea (CDU), attenuated vascular smooth muscle cell proliferation. 9 However, they later demonstrated that the antiproliferative effect of CDU is independent of EETs and s-EH.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the relationship between eNOS and SDF-1␣, because SDF-1␣ has been reported to have a deep relationship to NO synthase. 8 Immunohistochemical analysis showed that CD31-positive endothelium was hardly observed in the inner layer of the injured vessels 3 days after injury, in which colocalization of aggregated platelets and SDF-1␣ was observed (supplemental Figure IIA). Consistent with this finding, the expression level of eNOS mRNA was much lower in the wire-injured vessels compared with the uninjured contralateral vessels, and the expression levels of eNOS mRNA in the wire-injured vessels did not differ between BM-Agtr1 ϩ/ϩ and BM-Agtr1 Ϫ/Ϫ mice (supplemental Figure IIB).…”
mentioning
confidence: 98%